Nacimiento por cesárea como factor de riesgo para el desarrollo de asma bronquial en niños de 5 a 12 años. Hospital Belén de Trujillo - Mariños Malón, Angie Priscila (2017)
Objective: To determine if cesarean section is a risk factor for the development of bronchial asthma in children aged 5 to 12 treated in “Hospital Belén de Trujillo”. Methods: Case-control study, it was formed of children’s clinical records between 5 and 12 years of age borned and treated in the Outpatient basis of Hospital Belén de Trujillo during the years 2010 - 2014 with diagnosis of bronchial asthma for the cases and without diagnosis bronchial asthma for controls; clinical histories of children with a history of preterm birth with mothers in whose gestation they consumed tobacco and with passive exposure to tobacco during gestation were excluded. Results: Of the total number of children diagnosed with bronchial asthma, 59.1% had cesarean birth and 40.9% did not present it. The Odds Ratio (OR) was 2.12 with a 95% Confidence Interval (CI): <1.65 - 2.71>, p <0.05. Conclusions: There is an association between cesarean birth and development of bronchial asthma in children 5 to 12 years of age